Global Imbalances : In Midstream? - Milesi-Ferretti, Gian (IMF Staff Position Notes; Staff Position Note, 2009)
This chapter analyses various reasons for global imbalances and ways to tackle these issues. Current account balances reflect a plethora of macroeconomic and financial mechanisms. The overall assessment is that the pre-crisis policy advice and the conclusions from the Multilateral Consultations still largely hold. Namely, it is important to address domestic and systemic distortions. It is recommended to increase private and public US saving. The private part has largely taken place. The public part will have to take place over time. This will be good for the United States and help global rebalancing. In the fallout from the financial crisis, the adjustment process of global imbalances has started. However, stopping in midstream is dangerous-while imbalances are smaller than they used to be, the world economy is fragile. Failure to act on the remaining domestic and systemic distortions that caused imbalances would threaten the nascent recovery.